ADRENOCORTICOTROPIN-INDEPENDENT CUSHING’S SYNDROME DUE TO BILATERAL ADRENAL HYPERPLASIA: A RARE CASE OF PRIMARY PIGMENTED NODULAR ADRENOCORTICAL DISEASE - Laurentika, Ira; Tarigan, Tri Juli Edi; Yunir, Em; Rizal, Agus; Matondang, Sahat; Pasaribu, Merci Monica; Harahap, Agnes Stephanie (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Cushing’s syndrome (CS) is defined as a constellation of signs and symptoms that result from prolonged exposure to cortisol. The most common cause of CS is excessive use of corticosteroids also called exogenous CS. Endogenous CS only accounts for less than 20%. Adrenocorticotropin (ACTH)-independent CS or adrenal CS is characterized by evidence of hypercortisolism with suppressed serum ACTH level. The most common cause of this condition is unilateral adenoma, while bilateral adrenal hyperplasia is a rare cause. The two types of bilateral adrenal hyperplasia are primary bilateral macronodular hyperplasia (PBMAH) and primary pigmented nodular adrenocortical disease (PPNAD). The treatment of choice for bilateral adrenal hyperplasia with overt CS is bilateral adrenalectomy. Here, we reported a 22-year-old Indonesian female with overt CS due to PPNAD. She subsequently underwent bilateral laparoscopic adrenalectomy.